ダイ19ジ ナンキョク チイキ カンソクタイ カイヨウ ブモン ホウコク - 小田, 勝之; オダ, カツユキ; 信国, 正勝; ノブクニ, マサカツ; Oda, Katsuyuki; Nobukuni, Masakatsu (1980)
P(論文) 第19次南極地域観測において,定常観測(1977-1978)として海上保安庁水路部の担当した海洋観測の結果を報告する. This report presents the results of oceanographic observations, which were carried out by the 19th Japanese Antarctic Research Expedition in 1977-1978. departmental bulletin paper